2006
DOI: 10.1097/01.tp.0000210009.96816.db
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Living-Related Kidney Transplantation on the Donor’s Life

Abstract: Seen from the donor's perspective, LDKT is a relatively safe procedure. However, increased rates of donors with mental distress and intra-familial conflicts emphasize the need for a careful selection process. Regular postdonation psychosocial screening and provision of specific interventions to those in need are recommended. Donors should not suffer from financial and occupational disadvantages resulting from donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 24 publications
11
95
3
3
Order By: Relevance
“…Donors with postoperative complications felt ignored by both hospital staff and family, similar to other studies reporting that donors "feel forgotten" after donation (3,8,11,16,18,37,38). Our study reinforces on a grander scale the need for improved attention afterward.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Donors with postoperative complications felt ignored by both hospital staff and family, similar to other studies reporting that donors "feel forgotten" after donation (3,8,11,16,18,37,38). Our study reinforces on a grander scale the need for improved attention afterward.…”
Section: Discussionsupporting
confidence: 75%
“…Most kidney donors experience psychosocial benefits, including improved self-esteem and donor-recipient relationships (1)(2)(3)(4)(5); likewise, most report no regrets (6,7) and reaffirm their decision to donate (3,(8)(9)(10)(11)(12)(13). However, these experiences are not universal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the subject was not extensively studied in the setting of LRLT. In a study of living-related kidney transplantation, Reimer et al (19) observed that the donation led to family conflict in 5 cases (10.6%) and divorce in 3 cases (6.4%). A United Kingdom study (20) of renal transplantation again examined the psychologic and social-cultural perspectives of live donation and determined that donation may lead to anxiety regarding marriage and marital failure, and affect the other members of the family.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,10,15 Studies have also consistently found that a small proportion of donors (<10%) regretted their decision to donate or would not donate again. 2,3,9,11,12 The proportion of donors who felt pressure to donate their kidney varied across studies. The major concerns of donors related to postoperative pain (with some donors reporting the surgery as the most painful experience ever encountered), length of recovery, recipient wellbeing, health, employment issues, financial problems, health risks and lifestyle restrictions.…”
Section: What Is the Evidence?mentioning
confidence: 99%
“…1 Live donors are not only at risk of physical adverse events including infection and loss of renal function in the remaining kidney but they may also experience psychosocial problems including anxiety, depression, regret and financial hardship. 2,3 The psychosocial evaluation of donors (pre-and posttransplant) is widely advocated; 4 however, there is a paucity of data on the process and content of psychosocial evaluations. For example, there are no set standards regarding who should conduct psychosocial evaluations (physician, psychiatrist, psychologist, medical social worker), whether evaluations should be mandatory, at what stage of the work-up evaluations should be conducted, at what time interval repeat evaluations should be performed and what criteria need to be met.…”
Section: Introductionmentioning
confidence: 99%